PEMBELAJARAN SEJARAH YANG MULTIKULTURAL: STUDI KASUS DAN PENDEKATAN KUALITATIF DALAM KONTEKS EDUKASI - Eriswandi (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
In multicultural societies like Indonesia, differences across various aspects indicate that each individual holds a unique perspective on diversity. These diverse viewpoints have the potential to lead to misunderstandings among ethnicities, religions, and cultures, which can result in conflicts. This study aims to analyze the integration of multicultural education in history learning. The research method employed is qualitative with a case study approach, involving informants selected through purposive sampling. Data collection includes observations, interviews, and documentation using interview sheets and questionnaires. Data analysis is conducted descriptively and qualitatively. The research findings indicate that multicultural integration in history learning strives to synchronize teaching methods by considering differences such as gender, social status, religion, race, and language. History teachers incorporate multicultural values like tolerance, pluralism, humanism, and democracy into their lessons. In conclusion, multicultural education is a crucial concept that history teachers must grasp to impart deep multicultural values to students, fostering a high level of tolerance in their communities and surroundings.